Komparasi Prediksi Saham: Teknikal Klasik dan Modern - Mardatillah, Nur Insani; Soraya, Zalkha; Nasrullah, Nasrullah (E-Jurnal Akuntansi; Vol 35 No 5 (2025), 2025)
This research aims to compare the accuracy levels of classical technical analysis and modern technical analysis in predicting stock price movements of the JII index from June to November 2024. Classical technical analysis utilizes candlestick patterns, while modern technical analysis employs the Moving Average Convergence Divergence (MACD) indicator. The study uses secondary data from official sources such as the Indonesia Stock Exchange and the Profits Anywhere application. The research sample includes all 30 stocks in the JII index. The results indicate that classical technical analysis achieves an accuracy of 93% with fewer but more precise signals, whereas modern technical analysis has an accuracy of 81% with a larger number of signals. The Mann-Whitney statistical test reveals no significant difference between the two analysis methods. This research is expected to enhance the understanding of appropriate technical analysis methods for investment decision-making. Future research is recommended to broaden the data scope and incorporate additional variables for more valid and representative results. Keywords: Technical Classic; Technical Modern; Candlestick Patterns; MACD; Accuracy